MANAJEMEN PENGELOLAAN SAMPAH DI TPA PUTRI CEMPO KOTA SURAKARTA - Novita Sari, Dwi; Djumiarti, Titik; Yuniningsih, Tri (Journal of Public Policy and Management Review, 2024)
Waste management is a series of activities to manage waste effectively, efficiently and sustainably. The waste management carried out by the Putri Cempo TPA is the process of collection, transportation and final processing at the Putri Cempo TPA by producing environmentally friendly renewable energy. This research aims to analyze good waste management to reduce waste generation at the Putri Cempo TPA in the process of implementing waste management and describe the supporting and inhibiting factors for waste management at the Putri Cempo TPA, Surakarta City. This research uses a qualitative descriptive method with data source retrieval techniques through interviews, observation and documentation methods. The results of this research reveal that the Surakarta City Environmental Service has demonstrated its role in managing waste so that it can be processed further so as to provide benefits to the environment by using management functions according to G.R Terry, namely planning, organizing, actuating and controlling. Efforts made to reduce waste generation require a good waste management program by utilizing waste that has value which has been implemented by the Putri Cempo TPA, namely managing waste into renewable energy, namely producing electrical energy. Waste management still needs to be improved by providing outreach to the community by implementing waste recycling methods to reduce waste generation.